Physical Activities and Construct of Health Belief Models in the Special Region of Yogyakarta in the Era of Pandemy Covid-19 - Arika Umi Zar'in; Novita Intan Arovah (BIRCU, 2021)
This study aims to determine (1) the pattern, level and status of physical activity, (2) differences in the level of physical activity based on the construct status of the health belief model and (3) the relationship between physical activity status and the construct status of the health belief model in the people of the Special Region of Yogyakarta. This research is a cross-sectional observational survey research on the DIY community as many as 390 people using convenience sampling technique with online questionnaire. Physical activity is measured using the Global Physical activity Questionnaire (GPAQ) which calculates the metabolic equivalent of task (MetS) per week, while the health belief model construct is measured using the adaptation instrument from the COVID-19 snapshoot and monitoring (COSMO-WHO). The pattern of physical activity is seen by the level of physical activity in three domains (work, transport and leisure or recreation). The difference in the level of total physical activity in the construct of health belief model uses kruskall-wallis, while the relationship between physical activity status and constructs in health belief is tested by using chi square with a confidence level of 5%. The results of this study indicate that the physical activity pattern of the DIY community is dominated by recreational activities, with an average of 868.37 Mets / week, followed by the work domain with an average of 521.28 Mets / week and the transport domain with an average of 233.54 Mets / week. People who fall into the category of moderate physical activity status are 71%. DIY people who have a high level of HBM status tend to have sufficient physical activity status with a sig value of 0,000 in all constructs. It can be concluded that there is a relationship between the HBM construct and the physical activity status in the new normal era in the DIY community with high HBM status, so they will have a better level of physical activity status than those who have low HBM status, with a correlation value of 0.89 which meaning very strong.